SUBCUTANEOUS FAT NECROSIS OF THE NEWBORN - Alves, Rubina (2016)
Subcutaneous fat necrosis of the newborn (SCFN) is an uncommon disorder characterized by panniculitis, that usually runs a self-limited course and occurs in healthy and full-term newborn. The exact pathogenesis of subcutaneous fat necrosis of the newborn in not known, but it is postulated that cold or stress-induced injury to immature fat results in the development of solidification and necrosis; a granulomatous infiltrate forms subsequently. The present case report represents a SCFN limited to cutaneous involvement. The probable causal factor was delivery by cesarean.